Converged Biofabrication: Simultaneous Micropatterning of Fibrous Meshes and Bioinks for the Fabrication of Living Tissue Constructs (Adv. Healthcare Mater. 7/2019). Issue 7 (10th April 2019) - de Ruijter, Mylène; Ribeiro, Alexandre; Dokter, Inge; Castilho, Miguel; Malda, Jos
Abstract : In article number1800418, Miguel Castilho, Jos Malda, and co‐workers demonstrate how micropatterning of fibrous meshes and bioinks in a one‐step approach enables more control over cell and fiber deposition. This control over both the fibrous and cellular part is promising for the fabrication of living tissue constructs. The reinforcing effect of the fibers is present. Furthermore, viability and chondrogenic differentiation of mesenchymal stromal cells are not affected by the fabrication process.